Exploring Subordinate Clauses In The Story Of An Hour - Nazara, Wa’özisökhi (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2024)
This is a brief analysis of subordinate clauses found in Kate Chopin’s The Story of an Hour. Three types of clauses were identified according to their function within the complex sentences to which they belong. The three types are complement clauses, relative clauses, and adverbial clauses. Complement clauses are marked by that. Relative clauses are introduced by that, who, which, or whose. Adverbial clauses are marked by as or when. In terms of their structural types, two types of clauses were found: finite and non-finite clauses.